2004
DOI: 10.1177/0892705704035405
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Wood Fiber Polystyrene Composites: Processing–Structure–Mechanical Properties Relationships

Abstract: In this study, processing-structure-mechanical properties relationships in expanded wood fiber polystyrene composites (EPSC) made with a physical blowing agent were investigated. A systematic investigation was performed based on a statistical experimental design. The samples were saturated with carbon dioxide at high pressure and ambient temperature and the saturated specimens were expanded at elevated temperatures. The relations between impact and tensile properties of EPSC and foaming process and structure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 9 publications
0
25
0
Order By: Relevance
“…The temperature interval for the first decomposition step therefore associated to not only to the decomposition of WF but to the decomposition of IFR too [31,32]. Decomposition of APP releases nonflammable gases such as NH 3 and H 2 O. Shumao et al [33] investigated the flame retardancy and mechanical properties of ramie-fiberreinforced poly(lactic acid) biocomposites with the addition of APP.…”
Section: Thermal Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The temperature interval for the first decomposition step therefore associated to not only to the decomposition of WF but to the decomposition of IFR too [31,32]. Decomposition of APP releases nonflammable gases such as NH 3 and H 2 O. Shumao et al [33] investigated the flame retardancy and mechanical properties of ramie-fiberreinforced poly(lactic acid) biocomposites with the addition of APP.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…An example of positive attributes of thermoplastics is the ability to be processed with injection molding and extrusion which allows the production of WPC products for various applications. The most commonly used thermoplastics in manufacturing WPCs are polyethylene (PE) [1], polypropylene (PP) [2], polystyrene (PS) [3], and polyvinyl chloride [4]. The most commonly used thermoplastics in manufacturing WPCs are polyethylene (PE) [1], polypropylene (PP) [2], polystyrene (PS) [3], and polyvinyl chloride [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rizvi et al 9 observed that the presence of moisture and extractives in wood particles contribute to the initiation of cell nucleation. The volatilization of moisture and extractives from vegetable fibers occuring below 175°C (which is the customary processing temperature) generates a small amount of gas, which generally migrates to the polymer-fiber interfacial region and thereby initiates the 10 reported that different cellular morphologies can be obtained depending on the type, size and concentration of the vegetable fiber used in the cellular composite. Expanded composites can undergo large compressive deformations and thus absorb considerable amounts of specific energy.…”
Section: Introductionmentioning
confidence: 99%
“…The mixed powders were uniaxially die-pressed into compacts, followed by slowly heating to 500 °C to burn off the PVB particles and other organic binders. After densification sintering at 1200 °C, porous HA ceramics were produced with pores formerly occupied by PVB, as shown in is one of important polystyrene products [118,119]. EPS is usually white and made of expanded polystyrene beads as shown in Figure 2-15.…”
Section: Coral Replamineform Methodsmentioning
confidence: 99%